Effect of Combined Heat‐Moisture/Lactic Acid Treatment on the Physicochemical and In Vitro Digestibility Properties of Corn Starch. (20th October 2020) - Reyes, Isabel; Hernandez‐Jaimes, Carmen; Meraz, Monica; Vernon‐Carter, E. Jaime; Alvarez‐Ramirez, Jose
Abstract: Native corn starch is subjected to dual heat moisture (30 g per 100 g d.b.)/lactic acid (10 g per 100 g d.b.) treatment (HMLAx) at different temperatures ( x = 90, 110, 130, and 150 °C), and is compared with heat moisture (HMx) treatment alone. Neither HMLAx nor HMx change the crystallinity type (A‐type) of the corn starch, but the relative crystallinity is lowered by 60–80%. Both treatments reduce the gelatinization enthalpy, but it is higher for HMLAx (≈70%), and induces reductions in rapidly digestible starch (up to ≈70%) and increases in slowly digestible starch (up to ≈35%) and resistant starch (RS) fractions. The variations are temperature dependent. A principal component analysis is carried out (9 formulations, 17 variables), showing that heat moisture and lactic acid act independently ( p < 55%) in the modification of starch, giving rise to different physicochemical (solubility, viscoelasticity, relative crystallinity), thermal, and in vitro digestibility properties. Abstract : Corn starch is subjected to thermal and lactic acid treatment. Lactic acid hydrolysis has the largest effect on starch structure. Modified corn starch shows reduced in vitro digestibility properties.